Self-Workplace Inspection Information System - Cheong Chun Pin; Shahreen Kasim (Applied Information Technology And Computer Science, 2023)
The Self-Workplace Inspection Information System is a data management system built for Sawit Kinabalu Sdn Bhd that helps to improve business processes that still use Excel sheets for manually filled assessments. The system was developed to improve the business process of the operating unit in recording inspection compliance status, carrying out a comprehensive report, and making sure all the inspection aspects are in good shape. The target user of the system is the operating unit manager, inspection officer, admin, and the sustainability unit with 5 modules provided. Throughout this project, the agile scrum approach has been applied, and PHP with the Laravel framework and XAMPP has been used to construct the system. This developed system can be able to help provide efficiency to the operating unit and staff activity on inspections.